2018
DOI: 10.3892/ol.2018.8384
|View full text |Cite
|
Sign up to set email alerts
|

Grading of pancreatic neuroendocrine neoplasms using pharmacokinetic parameters derived from dynamic contrast‑enhanced MRI

Abstract: The present study aimed to evaluate the diagnostic efficacy of pharmacokinetic parameters derived from dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in prospective evaluation of pancreatic neuroendocrine neoplasms (pNENs) grading. A total of 25 histologically proven patients with pNENs (30 lesions in total) who underwent DCE-MRI were enrolled. Lesions were divided into G1, G2 neuroendocrine tumor (NET) and G3 NET/neuroendocrine carcinoma (NEC) groups based on their histological findings accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The use of imaging analysis for the grading and prognosis assessment of NEN patients has been investigated by other groups. In a recent study by Zhao et al, pharmacokinetic parameters of dynamic contrast-enhanced magnetic resonance imaging were found to be predictive of NET grading, helping to distinguish between G1 and G2 tumors [33]. Another study reported that CT texture analysis and CT features were predictive of pancreatic NET aggressiveness and could be used to identify patients at risk of early disease progression after surgical resection [34].…”
Section: Discussionmentioning
confidence: 99%
“…The use of imaging analysis for the grading and prognosis assessment of NEN patients has been investigated by other groups. In a recent study by Zhao et al, pharmacokinetic parameters of dynamic contrast-enhanced magnetic resonance imaging were found to be predictive of NET grading, helping to distinguish between G1 and G2 tumors [33]. Another study reported that CT texture analysis and CT features were predictive of pancreatic NET aggressiveness and could be used to identify patients at risk of early disease progression after surgical resection [34].…”
Section: Discussionmentioning
confidence: 99%
“…3.378 ± 0.378, respectively; p = 0.045) 64. Furthermore, the quantitative values of Ktrans and the contrast rate between the extracellular extravascular space and the vascular space (kep), are helpful for differentiating G2 NET from G1 ones 65…”
Section: Introductionmentioning
confidence: 99%
“…Reports from multiple centers worldwide began to challenge the notion that these lesions were biologically indistinct from their poorly-differentiated counterparts, especially with respect to responsiveness to chemotherapies. [3][4][5][6] In 2017, the classification for PNETs was updated to acknowledge that highly-proliferative PNETs should be treated differently if they are well-differentiated tumors (NETG3) compared to carcinomas (NECs).…”
Section: Introductionmentioning
confidence: 99%